Further evaluation of treatment integrity for response interruption and redirection. (19th August 2020) - Gauthier, Kimberly A.; Ahearn, William H.; Colón, Candice L.
Abstract: A few studies on response blocking as well as response interruption and redirection (RIRD) as a treatment for automatically maintained problem behavior have examined different levels of treatment integrity. Results from these studies have shown continued suppression of responding under low levels of integrity for some participants after they were exposed to blocking at full integrity. The current study compared the treatment effects of RIRD at two levels of integrity (100 and 33%). The 33% condition was not preceded by exposure to full integrity. Four children diagnosed with an autism spectrum disorder between the ages of 8 and 16 participated. The effects of treatment integrity on vocal stereotypy were assessed using an ABAB‐variant design in which B consisted of an alternating‐treatments comparison of different levels of integrity. Results varied across participants, and although both conditions decreased stereotypy, 100% integrity produced lower levels of stereotypy quicker than 33%. The current study expands upon current literature by suggesting that lower levels of integrity (33%) may still suppress vocal stereotypy.